Environmental risk and decision analysis - Sholarin, E.; Awange, Joseph (2015)
© 2015, Springer International Publishing Switzerland. Environmental risk deals with the probability of an event causing a potentially undesirable effect.Environmental risk assessment thus deals with the statistics (both qualitative and quantitative), because probability is the mathematical measure of risk, and with hazard assessment, which determines the nature of the undesirable effect.